p75 Neurotrophin Receptor in the Skin: Beyond Its Neurotrophic Function - Pincelli, Carlo (Frontiers in Medicine, 2017)
p75NTR (CD271) is the low-affinity receptor that, together with the tyrosine kinase receptor Trk, mediate neurotrophin (NT) functions. Beside their classic role in skin innervation, NTs and their receptors constitute a complex cutaneous network associated with a number of autocrine and paracrine activities. In this context, the role of p75NTR is becoming more and more important. This review will focus on the intriguing functions of p75NTR in healthy and diseased skin. First, p75NTR counterbalances the proliferative and survival activities of its cognate receptor Trk by inducing keratinocyte apoptosis. In addition, p75NTR identifies an early transit-amplifying (TA) keratinocyte population, and plays a critical role in keratinocyte stem cell transition to its progeny as well as in epidermal differentiation. p75NTR is absent in psoriatic TA cells, thus rendering these cells resistant to apoptosis. On the other hand, p75NTR infection restores NT-induced apoptosis in psoriatic keratinocytes. Taken together, these results provide evidence for a critical role of p75NTR in epidermal homeostasis, while its lack may account for the TA defect in psoriasis. While the issue of p75NTR as a marker of melanoma initiating cells is still to be solved, there is strong evidence that down-regulation of this receptor is a precondition to melanoma invasion and metastasis in vitro and in vivo. All in all, this review points to p75NTR as a major actor in both physiologic and pathologic conditions at the skin level.